ANALISIS PEMANFAATAN HANDPHONE BAGI SISWA MA AL-MUJAHIDIN KECAMATAN BAGAN SINEMBAH KABUPATEN ROKAN HILIR T.A 2013/2014 - Nilawati '; Zulfan Saam Zulfan Saam; Abu ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
AbstractTitle of research are : Analysis of students' use of mobile stale MA AL - Mujahidin District of Chart Sinembah Rokan Hilir . The purpose of this study was 1 ) to examine the use of mobile phones in schools MA Al - Mujahidin Sinembah Chart District of Rokan Hilir.2 ) to examine the use of mobile phones outside of school MA Al - Mujahidin Chart Subdistrict District Sinembah Rokan Hilir. This research was conducted in MA Al - Mujahideen District of Chart Sinembah Rokan Hilir with quantitative descriptive method . Population many as 48 people , who were sampled entirely . Collecting data in this study using a questionnaire .The results of data analysis show that : 1 ) Students use mobile phones as a tool for motivation , 2 ) Students are more confident with their mobile phones , 3 ) Students MA Al - Mujahidin use mobile phones as a means of learning , 4 ) Students use the phone as a communication tool , 5 ) students use mobile phones as a means of entertainment .From the study it can be concluded that the utilization of mobile phones for students MA Al - Mujahidin District of Chart Sinembah Rokan Hilirin a school environment that is for motivation . Utilization of mobile phones for students to learn is easier to find information about the subject , as a means of calculating and storing the data subjects . outside the school as a communication tool and for entertainment . For students who have suggested that mobile phones can take advantage of the things that are useful and positive as to belajar.Bagi the school in this case suggested can lead students to the use of mobile phones does not interfere with the process of learning and teaching . Keywords : Mobile Phone